Ben Waller papers - Waller, Ben, active 1752-1754.
Affadavit (1752) signed by Waller stating that John Todd, a Dissenter, had taken proper oaths substituted for those of allegiance and supremacy to the British sovereign and was eligible to minister to Dissenter congregations. Also, an account for lace making by Elizabeth Wyatt for which she sought payment from Mary Grimes in a claim presented to and granted by Waller.
Jurist of Williamsburg, Va.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Todd, John, -- 1719-1793.; Grimes, Mary; Wyatt, Elizabeth; Dissenters, Religious -- Virginia; Lace and lace making -- Virginia; Williamsburg (Va.) -- Trials, litigation, etc; Virginia -- Trials, litigation, etc; Jurists